AAV-Mediated Gene Therapy for Glycosphingolipid Biosynthesis Deficiencies. Issue 6 (June 2021) - Yang, Huiya; Brown, Robert H.; Wang, Dan; Strauss, Kevin A.; Gao, Guangping
Abstract : De novo glycosphingolipid (GSL) biosynthesis defects cause severe neurological diseases, including hereditary sensory and autonomic neuropathy type 1A (HSAN1A), GM3 synthase deficiency, and hereditary spastic paraplegia type 26 (HSPG26), each lacking effective treatment. Recombinant adeno-associated virus (AAV)-mediated gene therapy has emerged as a powerful treatment for monogenic diseases and might be particularly suitable for these neurological conditions.